Biological Features of the Spotted Thicklip Loach, Triplophysa Strauchii, of the Chirchik River in Uz-Bekistan - M, Shomuratova; S. , Rakhmatova; F., Utemuratova; M., Yuldashov; B. , Kamilov (American Journal of Biology and Natural Sciences, 2024)
In May 2023, the biological features of the spotted thicklip loach (Triplophysa strauchii) were studied in the Chirchik River, Tashkent region, Uzbekistan. The fol-lowing meristic characters of loach were determined: D III-IV 7-9, A III 5, 11-17 rakers on the first gill arch. The body is naked. The caudal peduncle at the base (behind the anal fin) is not compressed from the sides. The nostrils are located close to each other. The plastic characters of the sloth bear are given. It reaches sexual maturity at a standard body length of 5-6 cm, a total body weight of 2-4_ g. The ratio of sexually mature females to males was 2.1: 1. Individual absolute fe-cundity was 240 - 5700 eggs. In May, in the gonads at the IV stage of maturity, the eggs were 0.3 - 0.9 mm in diameter. Small, non-commercial fish, numerous in the Chirchik River in the middle reaches.